Gambaran Dukungan Sosial Suami Dalam Rangka Pemeriksaan Inspeksi Visual Asam Asetat Di UPT. Puskesmas Dawan I - Ni Kadek Dina Ardani Asih; Ni Komang Yuni Rahyani; Ni Nyoman Sumiasih (Poltekkes Kemenkes Denpasar, 2020)
Cancer is an abnormal cell condition and grows out of control. The incident of cervical cancer can be lowered by having early detection of cervical cancer. One of facotrs that affects early detection is husbad’s support. This study aim to find out the description of husband’s social support on visual inspection with acetic acid (VIA). The primary data of this study were collected by using questionnaire with descriptive survery method research design. This study was conducted in Technical Implementing Unit (TIU) in Community Health Care Center of I Dawan on April 2019. The samples were 35 women of childbearing age aged 30 – 50 years old who were selected by applying consecutive sampling technique. The descriptive analysis result shows the frequency of those who did not have VIA are 21 respondents (60,0%). The higher frequency of informational support is the good category by 18 respondents (51,4%), instrumental support is the insufficient category by 19 respondents (54,3%), emotional support is the good category by 22 respondents (62,9%). In further, the result presents that husbands’ social supports on VIA are mostly on the insufficient category which is 18 respondents (51,4%). We need to concern in promotion effort to increase the target of early detection in cervical cancer.